2011
DOI: 10.1007/s10620-011-1714-y
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Specific Knowledge, Coping, and Adherence in Patients with Inflammatory Bowel Disease

Abstract: Greater IBD knowledge appears to be associated with the use of more adaptive coping strategies in patients with IBD, suggesting that providing disease-related patient education may enhance coping in this population. Future studies should explore the utility of formal disease-related patient education in improving these and other outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 27 publications
5
42
1
3
Order By: Relevance
“…Young patients, those with Crohn's disease and those with a first-degree relative with IBD also scored relatively highly, as patients did when the questionnaire developed by Jones et al was applied in clinical practice [5]. By contrast, the authors found no association between knowledge and either disease duration or quality of life and it is clear from other studies that, while education may be desirable from both the patients' and the healthcare professionals' viewpoint, knowledge itself does not necessarily translate into improved overall wellbeing [2,20,21]. The increasing use of IBD registries and databases has placed emphasis on collating large volumes of biological, psychological and socioeconomic data from patients [22,23] and such projects require validated and concise questionnaires to acquire reliable results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Young patients, those with Crohn's disease and those with a first-degree relative with IBD also scored relatively highly, as patients did when the questionnaire developed by Jones et al was applied in clinical practice [5]. By contrast, the authors found no association between knowledge and either disease duration or quality of life and it is clear from other studies that, while education may be desirable from both the patients' and the healthcare professionals' viewpoint, knowledge itself does not necessarily translate into improved overall wellbeing [2,20,21]. The increasing use of IBD registries and databases has placed emphasis on collating large volumes of biological, psychological and socioeconomic data from patients [22,23] and such projects require validated and concise questionnaires to acquire reliable results.…”
Section: Discussionmentioning
confidence: 92%
“…As with other chronic diseases, patient education is an important aspect of IBD care and may result in improved patient satisfaction and coping skills [1,2]. Most researchers agree that patients want to be provided with comprehensive information about their disease [3][4][5] and instruments to measure patient knowledge are therefore required both for research and for clinical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Disease-related knowledge can positively affect the acceptance of the disease, increase treatment compliance and improve the quality of life of patients with IBD (van der Eijk et al 2004, Husain & Triadafilopoulos 2004. Disease-related knowledge also allows patients to become more involved in decisions regarding the treatment of their disease and to achieve a better relationship with their IBD teams (Moradkhani et al 2011). In chronic diseases, such as CD and UC, information is essential for treatment adherence and the prevention of complications (Eaden et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These are the factors that acted as a catalyst to the development and implementation of a pilot group education programme within the northwest region of the UK. Yet, little is known about the effects of providing disease-related education within IBD 9. There is a paucity of data to support the clinical effectiveness and economic value of providing group patient education within IBD.…”
Section: Introductionmentioning
confidence: 99%